The Stock Selection and Performance of Buy-Side Analysts - Groysberg, Boris; Healy, Paul; Serafeim, George; Shanthikumar, Devin (Management Science, 2013)
Prior research on equity analysts focuses almost exclusively on those employed by sell-side investment banks and brokerage houses. Yet investment firms undertake their own buy-side research, and their analysts face different stock selection and recommendation incentives than their sell-side peers. We examine the selection and performance of stocks recommended by analysts at a large investment firm relative to those of sell-side analysts from mid-1997 to 2004. We find that the buy-side firm's analysts issue less optimistic recommendations for stocks with larger market capitalizations and lower return volatility than their sell-side peers, consistent with their facing fewer conflicts of interest and having a preference for liquid stocks. Tests with no controls for these effects indicate that annualized buy-side strong buy/buy recommendations underperform those for sell-side peers by 5.9% using market-adjusted returns and by 3.8% using four-factor model abnormal returns. However, these findings are driven by differences in the stocks recommended and their market capitalization. After controlling for these selection effects, we find no difference in the performance of the buy- and sell-side analysts' strong buy/buy recommendations. This paper was accepted by Mary Barth, accounting.